丁苯酞序贯治疗急性缺血性卒中有效性和安全性的meta分析Meta-Analysis of the Efficacy and Safety of Butylphthalide Sequential Treatment in Acute Ischemic Stroke - 胡燕琴，王铄，赵陶丽，郭东兴，李申，金振波 (HU Yanqin, WANG Shuo, ZHAO Taoli, GUO Dongxing, LI Shen, JIN Zhenbo) (Zhongguo cuzhong zazhi)
目的 系统评价丁苯酞序贯治疗急性缺血性卒中的有效性和安全性。 方法 计算机检索PubMed、Embase、Cochrane Library等英文数据库，以及万方、中国知网、维普等中文数据库，纳入丁苯酞序贯治疗急性缺血性卒中的RCT，检索时限为建库至2024年6月30日。采用Cochrane RevMan偏倚风险评估表评价纳入的RCT质量。提取各项RCT的基线信息、治疗信息，以及治疗的有效性指标[90 d预后良好（mRS评分0～2分）、治疗后神经功能状态（采用NIHSS评分）、治疗后功能状态（采用mRS评分）、治疗后日常生活活动（activity of daily living，ADL）评分]和安全性指标（不良事件和严重不良事件）。采用RevMan 5.3软件对上述指标进行meta分析，计算分类变量的OR值及其95%CI，以及连续变量的标准化均数差（standardized mean difference，SMD）值及其95%CI。 结果 本研究共纳入8项RCT的报告，其中英文报道的研究有3项，中文报道的研究有5项；共包括1911例患者，其中对照组932例，试验组979例。meta分析显示，与常规治疗相比，丁苯酞序贯治疗可提高急性缺血性卒中患者的90 d预后良好率（OR 1.41，95%CI 1.11～1.77，P=0.004），降低治疗后的mRS评分（SMD -0.85，95%CI -1.09～-0.60，P＜0.001）和NIHSS评分（SMD -0.95，95%CI -1.13～-O.77，P＜0.001），提高治疗后的ADL评分（SMD 1.26，95%CI 1.05～1.46，P＜0.001）。两组的不良事件发生率（OR 0.97，95%CI 0.76～1.24，P=0.80）和严重不良事件发生率（OR 0.83，95%CI 0.59～1.16，P=0.27）差异没有统计学意义。 结论 丁苯酞序贯治疗可改善急性缺血性卒中患者的预后、神经功能状态和ADL，且不增加不良事件的发生率。Abstract: Objective To systematically evaluate the efficacy and safety of butylphthalide sequential treatment in acute ischemic stroke. Methods This study searched English databases such as PubMed, Embase, and Cochrane Library, as well as Chinese databases such as Wanfang, CNKI, and VIP. RCTs of butylphthalide sequential treatment in acute ischemic stroke were included, with the search period covering the period from the inception of the databases to June 30, 2024. The Cochrane RevMan bias risk assessment tool was used to evaluate the quality of the included RCTs. Baseline information, treatment details, and efficacy indicators [rate of good prognosis (mRS score 0-2) at 90 days, post-treatment neurological status (assessed by NIHSS score), post-treatment functional status (assessed by mRS score), and post-treatment activity of daily living (ADL) score], and safety indicators (adverse events and serious adverse events) were extracted. Meta-analysis was conducted using RevMan 5.3 software to calculate the OR values and their 95%CI for categorical variables, and the standardized mean difference (SMD) values and their 95%CI for continuous data. Results This study included a total of 8 RCTs, with 3 reported in English and 5 in Chinese. It involved 1911 patients, including 932 in the control group and 979 in the experimental group. Meta-analysis showed that compared to conventional treatment, butylphthalide sequential treatment improved the 90-day good prognosis rate in acute ischemic stroke patients (OR 1.41, 95%CI 1.11-1.77, P=0.004), reduced the post-treatment mRS score (SMD -0.85, 95%CI -1.09--0.60, P<0.001) and NIHSS score (SMD -0.95, 95%CI -1.13--0.77, P<0.001), and increased the post-treatment ADL score (SMD 1.26, 95%CI 1.05-1.46, P<0.001). There was no statistically significant difference between the two groups in the incidence of adverse events (OR 0.97, 95%CI 0.76-1.24, P=0.80) or serious adverse events (OR 0.83, 95%CI 0.59-1.16, P=0.27). Conclusions Sequential treatment with butylphthalide can improve the prognosis, neurological function, and ADL of patients with acute ischemic stroke without increasing the incidence of adverse events.